Muslims and Non-Muslims’ Satisfaction of the Islamic Insurance in Malaysia: Application of the Extended Customer Satisfaction Analysis - Yukichika Kawata; Syed Ahmed Salman (Türkiye İslam İktisadı Dergisi)
Islamic insurance has a more value-added substance than conventional insurance, and it is the ultimate solution for anyone seeking financial protection for their potential misfortune. However, the penetration ratio has been low even in Muslim majority countries, including Malaysia. While some existing studies examined the factors that contribute to improving the penetration rate, almost no studies examined satisfaction as the primary target. This study conducted a questionnaire for both Muslims and non-Muslims in Malaysia to investigate the factors that determine the satisfaction of the conventional and Islamic insurances. The Snowball sampling method was used, and 396 responses were obtained from Muslim and non-Muslim insurance policyholders in Selangor and Kuala Lumpur. The extended version of the Customer Satisfaction (CS) analysis was developed and applied to the Malaysian insurance policyholders’ data. There are three main results in this study. First, the factors that determine both Muslims’ and non-Muslims’ satisfaction with insurance were different. Second, while non-Muslims in Malaysia were satisfied with both the conventional and Islamic insurances, Muslims were more confident with the Islamic insurance than conventional ones. Furthermore, the current Islamic insurance would be accepted with higher satisfaction by non Muslims than Muslims. Third, the extended CS analysis successfully detected factors that determined satisfaction for both the conventional and Islamic insurances, suggesting the extended CS analysis was effective.